Assuming you mean this:
f(x) = [(x^2-2)^2]*[(4-2x)]
Product rule:
f(x) = p*q
f'(x) = p*q' + q*p'
So use the product rule and also apply the chain rule:
f'(x) = (x^2 - 2)^2 * (-2) + (4 - 2x)(2(x^2 -2) * 2x)
= -2(x^2 - 2)^2 + (4 - 2x)(4x(x^2 - 2))
Take out the common term:
= (x^2 - 2) [-2(x^2 - 2) + (4x)(4 - 2x)]
= (x^2 - 2) (-2x^2 + 4 + 16x - 8x)
= (x^2 - 2) (-2x^2 + 8x + 4)
= -2(x^2 - 2)(x^2 - 4x - 2)
2007-07-15 10:07:06
·
answer #1
·
answered by whitesox09 7
·
1⤊
0⤋
Yep...sure is...but no one knows what your equation is without proper parenthesis use. Is (x^2-2) raised to the power of 2(4-2x) or is it just squared and multiplied by (4-2x)?
Come on people! Work with me!
2007-07-15 17:06:35
·
answer #2
·
answered by gebobs 6
·
0⤊
0⤋
It's not clear whether the power is just 2 or 2(4-2x). Lets us assume the power is 2.
u=(x^2-2)^2
v=(4-2x)
f'(x)=udv+vdu
=(x^2-2)^2(-2) + (4-2x)(2)(x^2-2)(2x)
=-2(x^2-2)+4x(4-2x)(x^2-2)
2007-07-15 17:09:13
·
answer #3
·
answered by cidyah 7
·
0⤊
0⤋
ya....ur looking for the derviative......hmmmm........
a(2x^a-2)^a-1(2ax^a-1) {2(4-2x)}+ (x^a2-2) -2
i think....... but i've done a question like this so....??? sorry
2007-07-15 17:02:17
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
you need to stop swearing! to F's is 2 to many!
2007-07-15 17:18:05
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
there are math blogs where people love to do problems, google it
2007-07-15 17:02:59
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
wow if i knew that i would be.........smart..
give me a second while i go check my oven for that pooper scooper....
*distracted...somthing shiny*
2007-07-15 17:03:42
·
answer #7
·
answered by Chariot 183 4
·
0⤊
0⤋